Maximal handgrip strength can predict maximal physical performance in patients with chronic fatigue. (March 2020) - Jammes, Yves; Stavris, Chloé; Charpin, Caroline; Rebaudet, Stanislas; Lagrange, Gerard; Retornaz, Frederique
Abstract: Background: Maximal handgrip strength is used to predict exercise performance in healthy older subjects and in patients with chronic obstructive pulmonary disease, breast cancer or cirrhosis. Our objective was to evaluate the ability of maximal handgrip strength to predict maximal exercise performance in patients with chronic fatigue. Methods: Sixty-six patients with myalgic encephalomyelitis/chronic fatigue syndrome and 32 patients with chronic fatigue but no diagnosis of myalgic encephalomyelitis/chronic fatigue syndrome were included. The maximal physical performance was measured on a cycle ergometer to measure the peak oxygen uptake and the maximal work rate. We searched for linear regressions between maximal handgrip strength and maximal performances. Findings: No significant differences in slopes and ordinates of regression lines were noted between patients with or without a diagnosis of myalgic encephalomyelitis/chronic fatigue syndrome, allowing to pool the data. Maximal handgrip strength was significantly and positively correlated with peak oxygen uptake and maximal work rate in all patients with chronic fatigue. Interpretation: We conclude that handgrip strength can predict maximal exercise performance in patients with chronic fatigue. Highlights: Patients with chronic fatigue have often difficulties to perform a maximal exercise test. Maximal handgrip strength was used to predict maximal exercise performance. We explored 98 severely fatigued patients, 66 of them with chronic fatigue syndrome. Handgrip strength was correlated with peak values of oxygen uptake and work rate. Thus, handgrip strength is helpful when an ergometric cycle test cannot be performed.